2021
DOI: 10.1108/jmh-06-2020-0035
|View full text |Cite
|
Sign up to set email alerts
|

Social economy advancement: from voluntary to secure organizational commitments to public benefit

Abstract: Purpose This paper aims to explain the development of the social economy by analyzing when, why and how the community interest company (CIC) legal structure was established in the UK. The CIC legal structure was designed for social enterprise to ensure that company assets are committed to public benefit in perpetuity. Design/methodology/approach This research paper uses archival data and semistructured interviews to analyze the historical development of the social economy, emergence of social enterprise and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 58 publications
(91 reference statements)
0
4
0
Order By: Relevance
“…The Norwegian transnational entrepreneurs, indeed, laid JMH 28,4 the foundations for an entrepreneurial ecosystem in Arkhangelsk (Acs et al, 2017), which partly persisted after many of the Norwegians and other Western European foreigners had been forced to leave the region due to the increasing political turbulence. Most notably, their social contributions (cf., Haugh, 2021) are worth mentioning: the Norwegian entrepreneurs portrayed in this paper engaged both in establishing bonding social capital (through their close connections within the local Norwegian and Western European diaspora communities) and in bridging social capital (through their loose connections with the local Russians populace, including the authorities and local politicians) (cf., Anderson and Jack, 2002). Through this diversified social capital established in the Russian region (cf., Eklinder-Frick et al, 2011), the Norwegian pioneers founded important social institutions that are still in use today and that convey their entrepreneurial spirit even two or three generations later.…”
Section: Discussionmentioning
confidence: 99%
“…The Norwegian transnational entrepreneurs, indeed, laid JMH 28,4 the foundations for an entrepreneurial ecosystem in Arkhangelsk (Acs et al, 2017), which partly persisted after many of the Norwegians and other Western European foreigners had been forced to leave the region due to the increasing political turbulence. Most notably, their social contributions (cf., Haugh, 2021) are worth mentioning: the Norwegian entrepreneurs portrayed in this paper engaged both in establishing bonding social capital (through their close connections within the local Norwegian and Western European diaspora communities) and in bridging social capital (through their loose connections with the local Russians populace, including the authorities and local politicians) (cf., Anderson and Jack, 2002). Through this diversified social capital established in the Russian region (cf., Eklinder-Frick et al, 2011), the Norwegian pioneers founded important social institutions that are still in use today and that convey their entrepreneurial spirit even two or three generations later.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been shown that such 'alternative circuits' (Moulaert and Ailenei, 2005) institutional initiatives that offer solutions to social and environmental problems beyond those produced by the state and the markethave been a common occurrence throughout history (Galera and Borzaga, 2009). While these analyses are typically linked to social sector contexts (Pinch and Sunley, 2015;Haugh, 2021), CFEs provide an example of how the social enterprise literature could leverage these approaches to provide insights on the historical progression of novel organizational forms that address sustainability in the natural resource sector.…”
Section: Discussionmentioning
confidence: 99%
“…The experts, with volunteers from the NGOs, initiated a large number of projects dedicated to vulnerable persons, unemployed persons, disabled persons who had to work according to their capacity, unprotected children, domestic violence, etc. Step by step, these initiatives turned out to be a commitment to public benefit (Haugh, 2020) for a long-lasting development for communities and their citizens.…”
Section: Perspectives Of Romanian Social Economy As a European Countrymentioning
confidence: 99%